Percutaneous tracheostomy: comparison of Ciaglia and Griggs techniques - Añón, José M (BioMed Central, 2000)
BACKGROUND: Although the standard tracheostomy described in 1909 by Jackson has been extensively used in critical patients, a more simple procedure that can be performed at the bedside is needed. Since 1957 several different types of percutaneous tracheostomy technique have been described. The purpose of the present study was to compare two bedside percutaneous tracheostomy techniques: percutaneous dilatational tracheostomy (PDT) and the guidewire dilating forceps (GWDF). MATERIALS AND METHODS: A prospective study in two medical/surgical intensive care units (ICUs) was carried out. Sixty-three critically ill patients who required endotracheal intubation for longer than 15 days were consecutively selected to undergo PDT (25 patients) or GWDF (38 patients) technique. Intraoperative and postoperative complications were recorded. RESULTS: Age (mean ± standard error) was 63 ± 1.1 years. The patients had been mechanically ventilated for an average of 19.8 ± 1.2 days. The GWDF technique was significantly faster than PDT technique (P = 0.02). Fifteen complications occurred in 10 out of 63 (15%) patients. They were as follows: tracheal tear (one patient in each group; in one case this was due to false passage); transient hypotension (one patient in the PDT group and two patients in the GWDF group); atelectasis (one patient in the PDT group); and haemorrhage (one patient in the PDT group and three patients in the GWDF group). In both patients with tracheal tear, reduced arterial oxygen saturation (SaO(2)) with concomitant subcutaneous emphysema ensued. CONCLUSION: We found no statistical differences between complications with both techniques. The surgical time required for the GWDF technique was less than that for PDT.